Twistors and the Amplitudes in the Integrable Sector of Superstring Theory (Bulletin of Pure and Applied Sciences – Physics, 2021)
Twistors can represent the spin in superstring theory and provide a theoretical explanation of  the two-dimensional spherical model of elementary particles together with the surface  distributions of the charges. The integrability of certain matter sectors of the strong  interactions also may be traced to the action of the conformal group on collinear trajectories  that occur in a twistor formulation. The amplitudes for these scattering processes in four  dimensions have a representation with quantum states in a nonsupersymmetric theory defined  by the low-energy limit of a solution to the N = 2 string equations with a Wick rotation of the  metric with (2, 2) signature. The twistor form of an N = 2 scattering amplitude is given.